2021
DOI: 10.1038/s41467-020-20587-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective filling of n-hexane in a tight nanopore

Abstract: Molecular sieving may occur when two molecules compete for a nanopore. In nearly all known examples, the nanopore is larger than the molecule that selectively enters the pore. Here, we experimentally demonstrate the ability of single-wall carbon nanotubes with a van der Waals pore size of 0.42 nm to separate n-hexane from cyclohexane—despite the fact that both molecules have kinetic diameters larger than the rigid nanopore. This unexpected finding challenges our current understanding of nanopore selectivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 38 publications
2
57
0
Order By: Relevance
“…In agreement with the EA-SWCNTs, if PFO-BPy wrapping imparts a 1–2 cm –1 shift relative to surfactant samples the two RBM modes for the H 2 O@(6,5) samples can be assigned to (6,5) with water filling (313.8 cm –1 ) and empty (310.7 cm –1 ) . Here once again it is important to state that Qu et al recently showed that linear molecules present in trace amounts in the toluene can fill (6,5) and that these may also be associated with the peak at 310.7 cm –1 . The supernatant from the raw soot was found to only contain the peak at 310.7 cm –1 .…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In agreement with the EA-SWCNTs, if PFO-BPy wrapping imparts a 1–2 cm –1 shift relative to surfactant samples the two RBM modes for the H 2 O@(6,5) samples can be assigned to (6,5) with water filling (313.8 cm –1 ) and empty (310.7 cm –1 ) . Here once again it is important to state that Qu et al recently showed that linear molecules present in trace amounts in the toluene can fill (6,5) and that these may also be associated with the peak at 310.7 cm –1 . The supernatant from the raw soot was found to only contain the peak at 310.7 cm –1 .…”
Section: Resultssupporting
confidence: 66%
“…The use of polymer wrapping to separate (6,5) from the CoMoCAT raw soot is arguably the more common use of PFO-BPy within the scientific community, ,,, and it is thus the second example we provide. The small diameter of (6,5) now prevents the ingress of toluene, and a linear chain of water is obtained when filled. , Recently Qu et al showed that n -hexane and cyclohexane, which have kinetic diameters (KD) of ∼0.43 and ∼0.60 nm, respectively, can fit inside SWCNTs with a diameter of >0.78 nm, whereas only n -hexane is able to fit inside the next smallest species [(6,5) with d t = 0.76 nm] by elongating its structure. Toluene has a KD of 0.585 nm with a structure similar to that of cyclohexane, and thus it should behave similarly.…”
Section: Resultsmentioning
confidence: 99%
“…The inner surface of SWCNTs has a suitable curvature and large contacting area, which are particularly attractive in host–guest chemistry triggered by electron transfer. The endohedral volume of large-diameter SWCNTs beyond 1 nm provides a scaffold for encapsulating various types of molecules and materials. It is worth noting that the endohedral volume of SWCNTs is important for sorting nanotubes, because the open-ended nanotubes can be potentially filled by the solvent (e.g., water) during sonication and, thus, will affect nanotube separation based on density/buoyancy differences. , Inspired by this, we aim to modulate the charge density of the tube walls by encapsulating certain kind of molecules into the cavities and consequently control the intertube π–π stacking. Polyoxometalates are composed of cations and polyanion clusters with well-defined compositions and structures.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Capillary condensation of hexane has been studied inside sub-10 nm pores, where phase changes leading to confinement induced vapor pressure elevation were observed. 34 Selective filling of hexane inside single walled carbon nanotubes was demonstrated, 35 despite the diameter of the nanotubes being smaller than the kinetic diameter of hexane. Apart from the atmospheric contaminants, the flow of fluids in confined channels can be altered by other contaminants such as polymeric residues arising from fabrication processes and by amorphous carbon deposits when using chemically synthesized 2D materials.…”
Section: Introductionmentioning
confidence: 99%